2001
DOI: 10.1002/cncr.9046
|View full text |Cite
|
Sign up to set email alerts
|

Immediate on-site interpretation of fine-needle aspiration smears

Abstract: Objective To determine the venous and arterial hemodynamics underlying macrosomic fetal growth. Methods Fifty‐eight healthy women who previously had given birth to a large neonate were included in a prospective longitudinal study. Of these, 29 gave birth to neonates with birth weight ≥ 90th percentile and were included in the statistical analysis. Umbilical vein blood flow and Doppler measurements of the ductus venosus, left portal vein and the hepatic, splenic, superior mesenteric, cerebral and umbilical arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
156
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(162 citation statements)
references
References 22 publications
4
156
0
2
Order By: Relevance
“…Only when the cytopathologist personally performs the aspirate and immediately interprets it is adequate compensation for these professional services rendered. 17 Therefore, it is unlikely that this service will be maintained at all institutions. In cases in which USgFNA has to be performed without a cytologist present, it may be useful to emphasize that 5 passes will be diagnostic in 81% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only when the cytopathologist personally performs the aspirate and immediately interprets it is adequate compensation for these professional services rendered. 17 Therefore, it is unlikely that this service will be maintained at all institutions. In cases in which USgFNA has to be performed without a cytologist present, it may be useful to emphasize that 5 passes will be diagnostic in 81% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[144][145][146] The presence of a cytopathologist in the examination room is also debated, although most published studies showed an increased accuracy when a cytopathologist is available during the procedure. [147][148][149][150] An experienced cytopathologist, as well as the direct communication with the endoscopists, are essential for the success of the procedure. 151 Several large reports reported a complication rate of 1-2% for EUS-FNA.…”
Section: Eus-fnamentioning
confidence: 99%
“…With better training and experience, cytotechnologists can also assess the diagnostic accuracy of FNACs. Many studies have used ROSE to provide cytodiagnosis and have compared the results with those of histopathological diagnosis (4,5,9,10). However, we used ROSE only to check adequacy of the aspirated material.…”
Section: Discussionmentioning
confidence: 99%